Buncho poster color and water color: a new perspective / Mohd Zulhelmi Zainuddin - Zainuddin, Mohd Zulhelmi (2013)
This research focuses more on one of Buncho products which are the poster color and the water color. This research is made to figure out the reason why the longing of Buncho’s poster color and water color has decreased. This research is also to find out why these people tend to choose other products than Buncho.